2017
DOI: 10.1371/journal.pntd.0005393
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation and Hygiene (WASH) and environmental risk factors for soil-transmitted helminth intensity of infection in Timor-Leste, using real time PCR

Abstract: BackgroundNo investigations have been undertaken of risk factors for intensity of soil-transmitted helminth (STH) infection in Timor-Leste. This study provides the first analysis of risk factors for intensity of STH infection, as determined by quantitative PCR (qPCR), examining a broad range of water, sanitation and hygiene (WASH) and environmental factors, among communities in Manufahi District, Timor-Leste.MethodsA baseline cross-sectional survey of 18 communities was undertaken as part of a cluster randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 31 publications
(82 reference statements)
3
44
0
2
Order By: Relevance
“…Detailed characterization of participants at baseline, including environmental and WASH risk factors for STH infection, and intensity of infection are described elsewhere. 20,[30][31][32] Participation rates at each study time point were similar in the intervention and control arms and are shown in Supplemental Table 1. In total, 2,141 individuals (1,033 in the intervention arm and 1,108 in the control arm) participated in at least one follow-up time point, by completing a questionnaire and/or providing stool samples.…”
Section: Promoting Improved Household Sanitation By Increasingmentioning
confidence: 96%
“…Detailed characterization of participants at baseline, including environmental and WASH risk factors for STH infection, and intensity of infection are described elsewhere. 20,[30][31][32] Participation rates at each study time point were similar in the intervention and control arms and are shown in Supplemental Table 1. In total, 2,141 individuals (1,033 in the intervention arm and 1,108 in the control arm) participated in at least one follow-up time point, by completing a questionnaire and/or providing stool samples.…”
Section: Promoting Improved Household Sanitation By Increasingmentioning
confidence: 96%
“…Absence of evidence does not imply evidence of lack of WASH and helminth connection. The soil or aquatic life cycle requirements of STH and schistosomiasis leave no doubt that WASH is a key causal pathway to reduce environmental contamination and eventually break transmission [23]. New research should not try to re-establish this unassailable link, but rather should examine which WASH interventions are most effective at reducing exposure to infection, in which settings.…”
Section: Glossarymentioning
confidence: 99%
“…Oleh karena itu, program intervensi, preventif dan promosi kecacingan juga sangat perlu untuk dilaksanakan di tingkat desa untuk memberikan pemahaman kepada masyarakat tentang kerugian yang ditimbulkan oleh kecacingan. Perbaikan WASH (Water, Sanitation and Hygiene) yang diterapkan bersamaan dengan pemberian drug mass administration dinyatakan mampu memutuskan siklus hidup STH ledakan kasus tidak akan mampu diatasi hanya dengan pemberian anthelminthik, 14 hal ini dikarenakan obat cacing hanya mengurangi angka kesakitan sementara dan tidak memberikan efek pencegahan terhadap reinfeksi. 22…”
Section: Pendahuluanunclassified
“…WHO sendiri menargetkan peningkatan cakupan pemberian obat cacing dari 50% menjadi 75% pada tahun 2020 mendatang 3. dalam tubuh manusia 14,15. Infeksi A. lumbricoides dan T. trichiura menyebar melalui transmisi fecal-oral yang dimediasi oleh lingkungan yaitu melalui konsumsi telur/larva yang mengkontaminasi tanah.…”
unclassified